Ph treatment of pome via biological process – optimization - Anis Sakinah, Lokman Hakim (2014)
Palm oil mill effluent (POME) has been known as organic waste product from palm oil production which is featured by low pH of 3.5-4.5, high value of biological demand (BOD), chemical oxygen demand (COD) and suspended solids. It is found that palm oil industry is one of the contributors of environmental pollution if their waste not being treated well. So, it is mandatory for all palm oil mills to treat their wastewaters on site to an acceptable level before it is allowed to be discharged into the water courses. Biological treatment appears less cost than chemical and physical methods, and also much faster than natural oxidation, with a lower environmental impact. Thus, this study is aims to optimize the factors which are influencing biological pH treatment of acidic POME by using research surface methodology (RSM) with CCD response of Design Expert software via biological treatment of using soil mixed culture. In the beginning, the sample of acidic POME was collected from a nearby palm oil mill whereas soil mixed culture was obtained from soil near to plants root system. Preliminary study to obtain the best reaction time was done in 5th days and at the end, the utilization was performed better in between 3rd-4th days. Then, an acclimatization of soil mixed culture together with POME was conducted and 13 experimental runs were done according to RSM. Lastly, all the experimental results data will be optimized using RSM with factorial central composite design (CCD) using the software package Design Expert Version 6.0. The model showed that pH will increase upon increasing of agitation and temperature between to optimum conditions, but declined with further increases of these factors. From these optimum condition, it can be concluded that agitation and temperature had an individual significant influence on pH. Yet, the agitation and temperature was interdependent or having significant interaction on pH treatment while pH and temperature were interdependent according to the study and slightly interdependent and their interactive effects were insignificant. Based on the results, the predicted optimum condition suggested by software is temperature of 32.50 and agitation speed of 125 rpm. The expected pH value of 8.03 may obtained. Thus, the experimental response variables were very close to those predicted by RSM, indicating that RSM was a useful tool to optimize the pH treatment. Besides, the error generated was 2.293% indicated that the data was valid since the result does not excess 10%. After all, it can be concluded that the agitation speed and temperature were optimized to the optimum conditions and can be applied in industrial applications